2012
DOI: 10.1007/s00248-011-9999-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Associated Bacteria Throughout the Life Cycle of the Bark Beetle Dendroctonus rhizophagus Thomas and Bright (Curculionidae: Scolytinae) and Their Cellulolytic Activities

Abstract: Dendroctonus rhizophagus Thomas and Bright (Curculionidae: Scolytinae) is an endemic economically important insect of the Sierra Madre Occidental in Mexico. This bark beetle has an atypical behavior within the genus because just one beetle couple colonizes and kills seedlings and young trees of 11 pine species. In this work, the bacteria associated with the Dendroctonus rhizophagus gut were analyzed by culture-dependent and culture-independent methods. Analysis of 16S rRNA sequences amplified directly from iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 52 publications
9
119
1
1
Order By: Relevance
“…All isolates were active against carboxymethylcellulose; nevertheless, only a S. vestita isolate showed activity against filter paper. A study of the bacterial flora in the guts of Dendroctonus rhizophagus proposed that most of the bacterial genera that were present could be implicated in nitrogen fixation and cellulose breakdown, which are important roles associated with insect development and fitness, particularly given the challenging environment that is inhabited by bark beetles [10]. All of these results indicate that the bacteria in beetle hindguts play an important role in the degradation of plants and other organic matters that are consumed by D. armandi larvae.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…All isolates were active against carboxymethylcellulose; nevertheless, only a S. vestita isolate showed activity against filter paper. A study of the bacterial flora in the guts of Dendroctonus rhizophagus proposed that most of the bacterial genera that were present could be implicated in nitrogen fixation and cellulose breakdown, which are important roles associated with insect development and fitness, particularly given the challenging environment that is inhabited by bark beetles [10]. All of these results indicate that the bacteria in beetle hindguts play an important role in the degradation of plants and other organic matters that are consumed by D. armandi larvae.…”
Section: Resultsmentioning
confidence: 72%
“…Viable counting demonstrated that the population density of the cellulolytic bacteria in D. armandi larvae was 1.1 ± 0.46 × 10 2 CFU/gut, which was lower than that of other beetles, such as Saperda vestita (2.4 × 10 5 to 3.57 × 10 6 CFU/gut) [9] and D. rhizophagus (2.3 ± 0.43 × 10 3 CFU/gut) [10]. After one month of enrichment, the population density of the bacteria with CMCase activities was 1.5 ± 0.4 × 10 4 CFU/gut, which was also lower than that of other insects, such as Holotrichia parallela (1.14 ± 0.13 × 10 8 CFU/gut) and Pachnoda marginata (2.5 ± 1.1 × 10 8 CFU/mLgut) [4,22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metagenomic DNA obtained from the intestinal contents of fingerlings from control and probiotic treatments were used as a target for PCR amplification of V3 and V6-V8 regions of 16S rRNA gene. DGGE primers, PCR conditions, and DGGE general methodology were performed following directions previously described (Morales-Jiménez et al, 2012). PCR-DGGE profiles displayed by both 16S rRNA regions and the different experimental groups were grouped using Dice similarity coefficient and UPGMA hierarchical clustering method, the image analysis was made with the software Syngene (Synoptics Ltd., UK).…”
Section: Molecular Analysis Of Bacterial Communitiesmentioning
confidence: 99%